2022
DOI: 10.1158/1078-0432.ccr-20-3319
|View full text |Cite
|
Sign up to set email alerts
|

Anti–PD-1 Efficacy in Patients with Metastatic Urothelial Cancer Associates with Intratumoral Juxtaposition of T Helper-Type 1 and CD8+ T cells

Abstract: Purpose: PD-1 inhibition results in durable antitumor responses in a proportion of patients with metastatic urothelial cancer (mUC). The majority of patients, however, do not experience clinical benefit. In this study, we aimed to identify early changes in T-cell subsets that underlie anti–PD-1 efficacy in patients with mUC. Experimental Design: Paired samples were collected from peripheral blood, plasma, and metastatic lesio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
2
9
0
Order By: Relevance
“…The presented data extend our previous study on the frequency of T-cell subsets in blood samples of 56 out of these 71 patients with mUC (18). In this earlier study we demonstrated that responders harbor higher frequencies of CD4+ T-cells that express PD1 and 4-1BB when compared to non-responders at baseline, and responders showed changes in frequencies of these subsets during treatment.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The presented data extend our previous study on the frequency of T-cell subsets in blood samples of 56 out of these 71 patients with mUC (18). In this earlier study we demonstrated that responders harbor higher frequencies of CD4+ T-cells that express PD1 and 4-1BB when compared to non-responders at baseline, and responders showed changes in frequencies of these subsets during treatment.…”
Section: Discussionsupporting
confidence: 87%
“…In other words, we cannot support a direct relationship between a high MNTR in blood with tumor cell-entrapment by neutrophils in tumor tissue. Previously, we showed that a lack of CD4+ T helper type 1 (Th1) cells in the tumor at baseline, and their inability to cluster with CD8+ T-cells and myeloid cells upon treatment, were associated with resistance to pembrolizumab (18). Also, in case of the MNTR, it appeared that lack of CD4+ rather than CD8+ T-cells was predominantly associated with nonresponse and limited survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations